Motivação docente para educação inclusiva - Homem, Mariangela Pozza (2019)
The present work proposes a study on teacher motivation and inclusive education. The research presented here is justified by the scope of the theme and by the fact that much has been discussed about equal rights for all. The purpose of this proposal is to analyze how the effects of teacher motivation affect the school context of students with disabilities and / or special educational needs in the regular school system. As specific objectives we intend to mention, based on observations and data provided by the teachers, the reasons that are present in their pedagogical actions that contribute to this context; identify teacher motivational effects; to verify the strategies used by the teachers that contribute to this process. The methodology used is the multiple case study, with 11 teachers, in a private school in Porto Alegre. This study is based on a qualitative approach, using the semistructured interview, observations and data provided by the teachers in the daily classroom. One of the theoretical references used is Genetic Epistemology and the contributions of Vygotsky's Socio-historical theory (1999). It should be noted that the project also encompasses Vygotsky's (1999) ideas regarding the issue of development and the social relation of the individual. In relation to the studies of Inclusive Education, I am based on the studies of Mazzotta (1973), Januzzi (2006) Kassar (2008), Carvalho (2011), Rozek (2010), Baptista (2011), Mittler (2003). With regard to teacher training, Nóvoa (1995), Tardif (2012), Schön (1995), Sacristán (1998), and Pimenta (2011) and Carvalho (2011) allow a dialogue on the theme. The contributions came from different authors focused on the observation of teacher motivation such as Huertas (2001), Santos (2007), Jesus (1996), Deci and Ryan (2000) and Tapia (2015). I also emphasize the contributions of Freire (1980/2011) and Maturana and D'Avila (2009) in the studies of teaching practice. All authors served as a support for the interweaving of discursive textual analysis, contributing to the main focus of our research: the insertion of an inclusive perspective in our society. From the study, four categories were found, which contributed to the data analysis: teaching practice, school inclusion, continuing education and motivation. The conclusions indicate that teachers present knowledge about the reality of our inclusive schools, as well as the importance of teacher motivation in this process, in order to encourage the involvement and development of students with special educational needs and/or disabilities.